The last mile - Baldacci, David (New York : Grand Central Publishing, 2016)
Convicted murderer Melvin Mars is close to execution for killing his parents twenty years earlier. When another man confesses Mars is granted a reprieve. Amos Decker, newly hired on an FBI special task force, takes an interest in Mars's case after discovering the striking similarities to his own life: Both men were talented football players with promising careers cut short by tragedy. Both men's families were brutally murdered. And in both cases, another suspect confessed to the crime years later.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Decker, Amos (Fictitious character) -- Fiction; Football injuries -- Fiction; Large type books; Suspense fiction